Renewable Energy Systems to Enhance Buildings Thermal Performance and Decrease Construction Costs. (October 2018) - Albatayneh, Aiman; Alterman, Dariusz; Page, Adrian; Moghtaderi, Behdad
Abstract: Renewable energy systems can be used to improve the buildings thermal performance and to design sustainable buildings. To achieve maximum thermal comfort inside the housing test modules for all weather conditions without using any form of energy from fossil fuels which could be obtained from renewable energy systems. Different modules type (Cavity Brick (CB), Insulated Cavity Brick (InsCB), Insulated Brick Veneer (InsBV) and Insulated Reverse Brick Veneer (InsRBV)) with the type of renewable energy systems is performed to determine which type could provide the greatest energy savings with the least cost. InsCB the best performing module but it cost more to build while InsBV module cost less but with lower thermal performance which can be compensated by using Photovoltaic systems (PV) to enhance the thermal performance with the least cost.